The Pattern of Growth Circle in Otolith Motan Fish(T. thynnoides) in Teluk Petai Lake,BuluhNipis Village, SiakHuluSubdistrict, Kampar Regency, Riau Province. - Simarangkir, Lisa Meisim; Putra, Ridwan Manda; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMotan fish (Thynnichthys thynnoides) are found in the Bay of Petai Lake, Buluh Nipis Village, Kampar Regency. This study aims to examine the growth patterns exist in otolith. This research was conducted in March-April 2019. Sample fish were captured using gillnet and sempirai fishing gear. The sampled fish is 95 tails (59 males and 36 females). Otolith (sagita) is sharpened and the growth circle pattern is seen using a binocular microscope. The results of the study foundthatthe otolith length was 1,175-3,65 weight 0,0022-0,0178 g and the core distance to the first black circle ranged from 0.2-0.97 mm. This shows that the first dark circles are formed individually and the dark circle is not formed by periodic events in the life of motan fish. The number of dark circles on otolith is 1-3. Water quality recorded temperature 30,50C, brightness 76,25, pH 6, DO 6,44 mg/L, CO2 9,7.Keywords: Thynnichthys thynnoides, dark circles, growth patterns, sagita